Application of optical sensing system in heavy oil recovery. (February 2016) - Pan, Jingjun; You, Hongjuan; Pan, Yong; Wu, Di; Yu, Le; Wang, Xiaofei; Qiu, Xiaokang; Zhang, Min
Abstract: While the heavy oil recovery in China is switching from the traditional Cyclic Steam Stimulation to the more innovative Steam Assisted Gravity Drainage (SAGD), real-time reservoir monitoring system become more and more important for petroleum industries, but tradition electrical systems' performance on spatial resolution are not good enough. In this paper, we present an optical sensing system based on OTDR and corresponding interpretation, which can obtain the real-time temperature profile and its spatial resolution and temperature resolution is much higher than tradition electrical monitoring system. We utilized this system into the heavy oil recovery in Xinjiang oilfield, the experiment result shows that the position of steam cavity leading edge. This system can provide deep insight into the status of oil recovery process and provide basic data for the following operation.